Persepsi Kelompok Tani Alfa Omega Terhadap Penerapan Pertanian Organik Di Kelurahan Rurukan Kecamatan Tomohon Timur Kota Tomohon - Sembiring, Lida Devega Br; Tambas, Jane Sulinda; Loho, Agnes Estephina (Sam Ratulangi University, 2024)
The aim of the research was to determine the perception of the Alfa Omega farmer group regarding the implementation of organic farming in Rurukan Village, East Tomohon District, Tomohon City. This research lasted for three months from May to July 2023. The data used in primary data was obtained through interviews with 13 respondents from the Alfa Omega farmer group, which were taken by census and secondary data was obtained from agencies related to the research conducted. Data analysis used is descriptive. The results of the research show that the perception of the Alfa Omega farmer group regarding the implementation of organic farming is relative profit, namely profit if sold to shops that collaborate with the Alfa Omega farmer group, having good quality plants. The perception of suitability of plants is that they are suitable because of fertile soil, high soil moisture and good water access. The perception regarding the ease of trying it is that it is easy to implement organic farming and easy to get raw materials. The perception of complexity is that it takes a long time to neutralize the soil and it is difficult to get a clear price comparison on the market between organic agricultural products and non-organic products. There needs to be outreach so that the Alfa Omega farmer group implements organic farming. It is also hoped that the Department of Agriculture will provide financial assistance to be able to switch to organic farming.